Recycling of plastic: accounting of greenhouse gases and global warming contributions - Astrup, T.; Fruergaard, T.; Christensen, T.H.
Major greenhouse gas (GHG)emissions related to plastic waste recycling were evaluated with respect to three management alternatives: recycling of clean, single-type plastic, recycling of mixed/contaminated plastic, and use of plastic waste as fuel in industrial processes. Source-separated plastic waste was received at a material recovery facility (MRF)and processed for granulation and subsequent downstream use. In the three alternatives, plastic was assumed to be substituting virgin plastic in new products, wood in low-strength products (outdoor furniture, fences, etc.), and coal or fuel oil in the case of energy utilization. GHG accounting was organized in terms of indirect upstream emissions (e.g. provision of energy, fuels, and materials), direct emissions at the MRF (e.g. fuel combustion), and indirect downstream emissions (e.g. avoided emissions from production of virgin plastic, wood, or coal/oil). Combined, upstream and direct emissions were estimated to be roughly between 5 and 600 kg CO2-eq. tonne-1 of plastic waste depending on treatment at the MRF and CO2 emissions from electricity production. Potential downstream savings arising from substitution of virgin plastic, wood, and energy fuels were estimated to be around 60- 1600 kg CO2-eq. tonne-1 of plastic waste depending on substitution ratios and CO2 emissions from electricity production. Based on the reviewed data, it was concluded that substitution of virgin plastic should be preferred. If this is not viable due to a mixture of different plastic types and/or contamination, the plastic should be used for energy utilization. Recycling of plastic waste for substitution of other materials such as wood provided no savings with respect to global warming.
Keywords: PLASTIC RECYCLING; GLOBAL WARMING; CO2 ACCOUNTING; GREENHOUSE GASES; WASTE MANAGEMENT; ENERGY UTILIZATION